International Conference on Space Optics — ICSO 2012 2017
DOI: 10.1117/12.2309081
|View full text |Cite
|
Sign up to set email alerts
|

Radiation hardening of rare-earth doped fiber amplifiers

Abstract: Abstract-We investigated the radiation hardening of optical fiber amplifiers operating in space environments. Through a real-time analysis in active configuration, we evaluated the role of Ce in the improvement of the amplifier performance against ionizing radiations. Ce-codoping is an efficient hardening solution, acting both in the limitation of defects in the host glass matrix of RE-doped optical fibers and in the stabilization of lasing properties of the Er 3+ -ions. On the one hand, in the nearinfrared re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The optical fiber material can be radiation hardened by reducing the concentration impurities or using fluorine to adjust the silica refractive index [25]. However, other dopants are also interesting for this aspect, e.g., it was shown that the Ce-codoping of rare-earth-doped optical fibers efficiently limits the infrared RIA [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The optical fiber material can be radiation hardened by reducing the concentration impurities or using fluorine to adjust the silica refractive index [25]. However, other dopants are also interesting for this aspect, e.g., it was shown that the Ce-codoping of rare-earth-doped optical fibers efficiently limits the infrared RIA [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…However, whereas strong RIA reduction can be attained at signal wavelength [9], the insufficient RIA lowering at pump wavelength leads to complex Er-Yb double cladding optical fiber design, resulting in huge transparency power, thus to poor optical efficiency. Whereas such a fiber is suitable for specific high optical power applications, it cannot meet most satellite application requirements, in which power consumption is a key parameter.…”
Section: State Of the Artmentioning
confidence: 99%